Binder-free zeolite 4A for biogas upgrading and CO2 capture - Zafanelli, Lucas F.A.S. (2022)
To keep global warming below 2 ºC in the coming 30 years, the development and valorization of renewable sources of energy and also the CO2 capture from coal-fired power plants are important steps for the transition to a clean energy economy. Biogas is a sustainable and renewable source of energy from the anaerobic decomposition of organic matter and, together with natural gas, they are a more environmentally friendly alternative. The presence of CO2 in the biogas composition can reach up to 40 vol.%, which reduces biogas calorific value, impairs its transport via pipelines, and, consequently, limits its use [1]. CO2 released from coal-fired power plants has been contributing to a massive 73% of annual emissions for the energy sector [2]. This value could be reduced by attaching a recovery unit downstream of these power plants to recover CO2, avoiding its emissions. Among the processes available to recover CO2 and purify biogas, the adsorption is easy to operate, efficient to provide high recovery and purity, and more economical when compared to absorption and cryogenic separations, which have intensive energy consumption. Therefore, this work seeks to evaluate the adsorption equilibrium and dynamic separation of CO2, CH4, and N2 on binder-free zeolite 4A in conditions of interest to biogas upgrading and CO2 capture from the post-combustion stream.